Synthesis and characterization of ultra fine barium calcium titanate, barium strontium titanate and Ba1-2xCaxSrxTiO3 (x = 0.05, 0.10) - Rai A.K.; Rao K.N.; Vinoth Kumar L.; Mandal K.D. (My University, 2025)
Many desirable features can be brought in when certain ferroelectric materials are doped with calculated amount of foreign atoms. Ba1-2xCaxSrxTiO3 (BCST), Ba0.8Ca0.2TiO3 (BCT) and Ba0.8Sr0.2TiO3 (BST) have been synthesized via Pechini precursor route. It has been found that single phase was formed at 820-860 °C, which was confirmed by the XRD analysis. FTIR studies confirmed the presence of functional groups such as O-H, carboxylate ester and the carbonate in dry samples. Crystallite sizes of these ceramics were calculated by X-ray line broadening analysis, which were also confirmed by SEM studies. EDX studies confirmed the high purity of the synthesized materials. © 2008 Elsevier B.V. All rights reserved.